Genomic Microsatellite Signatures Identify Germline Mismatch Repair Deficiency and Risk of Cancer Onset. Issue 4 (1st February 2023) - Chung, Jiil; Negm, Logine; Bianchi, Vanessa; Stengs, Lucie; Das, Anirban; Liu, Zhihui Amy; Sudhaman, Sumedha; Aronson, Melyssa; Brunga, Ledia; Edwards, Melissa; Forster, Victoria; Komosa, Martin; et al.
Abstract : PURPOSE: Diagnosis of Mismatch Repair Deficiency (MMRD) is crucial for tumor management and early detection in patients with the cancer predisposition syndrome constitutional mismatch repair deficiency (CMMRD). Current diagnostic tools are cumbersome and inconsistent both in childhood cancers and in determining germline MMRD. PATIENTS AND METHODS: We developed and analyzed a functional Low-pass Genomic Instability Characterization (LOGIC) assay to detect MMRD. The diagnostic performance of LOGIC was compared with that of current established assays including tumor mutational burden, immunohistochemistry, and the microsatellite instability panel. LOGIC was then applied to various normal tissues of patients with CMMRD with comprehensive clinical data including age of cancer presentation. RESULTS: Overall, LOGIC was 100% sensitive and specific in detecting MMRD in childhood cancers (N = 376). It was more sensitive than the microsatellite instability panel (14%, P = 4.3 × 10 −12 ), immunohistochemistry (86%, P = 4.6 × 10 −3 ), or tumor mutational burden (80%, P = 9.1 × 10 −4 ). LOGIC was able to distinguish CMMRD from other cancer predisposition syndromes using blood and saliva DNA ( P < .0001, n = 277). In normal cells, MMRDness scores differed between tissues (GI > blood > brain), increased over time in the same individual, and revealed genotype-phenotype associations within the mismatch repair genes. Importantly, increased MMRDness score was associated with younger age of first cancer presentation in individuals with CMMRD ( P = 2.2 × 10 −5 ). CONCLUSION: LOGIC was a robust tool for the diagnosis of MMRD in multiple cancer types and in normal tissues. LOGIC may inform therapeutic cancer decisions, provide rapid diagnosis of germline MMRD, and support tailored surveillance for individuals with CMMRD.